Indanthrone derived disordered graphitic carbon as promising insertion anode for sodium ion battery with long cycle life - Suryawanshi, Anil; Mhamane, Dattakumar; Nagane, Satyawan; Patil, Shankar; Aravindan, Vanchiappan; Ogale, Satishchandra; Srinivasan, Madhavi (Electrochimica Acta, 2014)
We report facile, one step synthesis of disordered graphitic carbon by high temperature (1000 degrees C) pyrolysis of indanthrone dye (ID). The pyrolysed carbon is disordered in nature and the same is clearly evidenced by various analytical techniques like X-ray diffraction, Raman spectroscopy and high resolution transmission electron microscopy. Na-insertion properties of such indanthrone dye derived disordered graphitic carbon (IDDGC) is evaluated in half-cell assembly (Na/IDDGC). The test cell delivered a reversible capacity of similar to 160 mAh g(-1) at current density of 25 mAg 1. In addition, excellent cycling profiles are noted for such IDDGC, which retains 67% of initial reversible capacity after 500 cycles. The present study clearly highlights the importance of disorder in the graphitic carbon for efficient Na-ion storage. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: anode; disordered carbon; indanthrone; Na-ion battery